Peranan Ulama' Pesantren dalam Pendidikan Masyarakat; Potret Keulama'an KH.M.A. Sahal Mahfudz - Zumrotul Mukaffa (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
This paper seeks to see the role of Kyai Sahal in community education in his capacity as a scholars. His phenomenal figure became an interesting study in looking at the role of one scholars of these ‘Islamic boarding school’, in relation to educating the community to be empowered. Unlike the ‘Islamic boarding school’ scholars in general, Kyai Sahal not only educates people in the field of Islamic Religion, but more than that, it also controls the community through its involvement in two mass organizations of the Majelis Ulama’ Indonesia (MUI) and Nahdlatul Ulama’ (NU) problems that occur in society with the movement of small and medium economic empowerment, and make social changes through the social jurisprudence paradigm which leads him to have the view that the main purpose of the Shari’a is to prosper the ummah in the world and the hereafter. Man as the subject as well as object of Shari’a, is obliged to create prosperity of human life in the world for the prosperity of life in the afterlife.